The Analysis of Conversational Implicature Between Students and Teachers at Al-Azhar Islamic Boarding School - Akhmad Sofyan,; Riantino Yudistira,; Muta’allim,; Fahmi Reza Alfani,; Abdul Azizul Ghaffar, (RETORIKA: Jurnal Ilmu Bahasa, 2022)
Pesantren is an environment that is very well known as religiousness in which there are several rules that must be obeyed by teachers and students. The purpose of this discipline is to build humanist relationships. This study aims to uncover and describe the meanings and types of conversational implicatures contained in the conversations of teachers and students at the Salafiyah Syafi'iyah Al-Azhar Islamic boarding school. This study uses data analysis. Qualitative methods are methods that aim to obtain descriptive data. The data in this study are conversational implicatures that transcribed into written text. Data were collected using selection, description and verification techniques. Data were analyzed using qualitative descriptivewhich is based on Siswantoro's theory. The results of this study indicate that there are four types of conversation implicatures, namely general conversation implicatures, scaled implicatures, special conversation implicatures and conventional implicatures.